Differences in Teenage Women’s Motivation Score in The Prevention Of Adolescent Pregnancy Before and After Providing Health Education Through Video Media - Ni Made Desri Purwani; Ni Komang Yuni Rahyani; Ni Gusti Kompiang Sriasih (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Pregnancy among teenagers can have a bad effects on teenagers, both physically, psychologically, emotionally, and environmentally due to the unpreparedness of adolescent in facing their pregnancy, even to the point of causing death. This study aims to prove the difference in motivation scores of adolescent in avoid adolescent pregnancy before and after being given health education use video media. The type of research is pre-experimental with a one group pretest posttest design. The sample of this study were 58 girl students in grades X, XI and XII at SMA Negeri 2 Mengwi using a probability sampling technique, namely simple random sampling. Data analysis used the Wilcoxon test. The results of the study showed an increase in the average motivation score of adolescent before and after being given health education through video media (p value 0.000) with a mean rank of 9.21. These results indicate a difference in motivation scores of adolescent in avoid adolescent pregnancy before and after being given health education use video media. Further research is expected to be able to carry out different interventions regarding pregnancy prevention in adolescents.